O discurso sobre o gaúcho: uma análise enunciativa das músicas nativistas - Chagas, Nédilã Espindola (2011)
This work is part of the research line "Language, Subject and History" and proposes, from studies of enunciation, a discourse analysis about gaucho. This discourse is constituted as a reference source to a cultural movement called Nativism. In order to develop this analysis, we used the concept of Enunciation, postulated by Benveniste, and the concepts of Enunciation, Event, Temporality, Place of Enunciation and Interdiscourse, proposed by Guimarães. Moreover, we also used notions derived from Discourse Analysis, such as: Memory, Interdiscourse, Forgetting and Rememory. When considering that the establishment of a nativist discourse is produced through a rememory of Rio Grande do Sul historiography, we firstly reviewed the speeches of travelers and essayists in order to demonstrate that they constitute a set of ideas that reshape and resay in nativist discourse production. The nativist discourse comes with the Nativist Movement which, in turn, is part of the Traditionalist Movement, and these movements aim to maintain the gaucho culture and are used in this research as well as the founder event of Nativist Movement, Califórnia da Canção Nativa. As it is a discourse that is evident in both linguistic materiality and creation of meaning in terms of enunciation, the corpus of research is composed by three winning compositions in Califórnia da Canção Nativa. By analyzing this corpus, we tried to interpret the meanings that emerge from these statements by the rememory of other speeches, producing a crossover of speeches in the enunciative event of nativistic musics. In the nativistic compositions, speeches that helped form the gaucho as social type are retaken. However, in these compositions, the senses are different, are new, because, it happens in another time and space. The native gaucho is resignify for the timing of the event enunciation. Thus, the operation of the discourse reaffirms attributes, which previously meant the gaucho as distinct from the other Brazilians, to signify it as a symbol of regional identity, which authorizes it to be inserted into a national culture.